1995
DOI: 10.1007/bf02592364
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic effects on phagocyte chemiluminescence in vitro

Abstract: Phagocytes are an essential defence against infection. Since drugs which affect their function may alter the outcome of infections, we have studied the effect of nine antibiotics on phagocyte function in vitro. The effects of antibiotics on the respiratory burst function of phagocytes from healthy adult donors were investigated using lucigenin-enhanced chemiluminescence in response to serum-opsonised zymosan. Aminoglycosides showed dose-dependent suppression of polymorphonuclear leucocyte chemiluminescence, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Several investigators have reported a variety of effects of macrolide antibiotics on immunocompetent cells, inflammatory cells, and airway epithelial cells. It has been shown in in vitro studies that these drugs modulate the proliferation, differentiation, cytokine production, and phagocytosis of monocytes/macrophages, 11,22‐26 improves the ciliary movement of airway epithelium, 27 inhibits ion and mucus secretion from epithelial cells, 28,29 and inhibits bacterial adherence to nasal epithelial cells 30 . Furthermore, macrolide administration suppresses neutrophil exudation to inflammatory sites in patients with chronic upper and lower respiratory diseases 5,7‐9,13,17 …”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported a variety of effects of macrolide antibiotics on immunocompetent cells, inflammatory cells, and airway epithelial cells. It has been shown in in vitro studies that these drugs modulate the proliferation, differentiation, cytokine production, and phagocytosis of monocytes/macrophages, 11,22‐26 improves the ciliary movement of airway epithelium, 27 inhibits ion and mucus secretion from epithelial cells, 28,29 and inhibits bacterial adherence to nasal epithelial cells 30 . Furthermore, macrolide administration suppresses neutrophil exudation to inflammatory sites in patients with chronic upper and lower respiratory diseases 5,7‐9,13,17 …”
Section: Discussionmentioning
confidence: 99%
“…There are no available scientific reports regarding the influence of antibiotics on qualitative and quantitative changes in the subpopulations of immune cells in the uterus of cows. Most of the available literature presents the negative effects of many types of antibiotics on phagocytic cell activity, both in vitro and in vivo (Bode et al, ; Mor & Cohen, ; Pierce, Tarnow‐Mordi, & Cree, ). Research carried out by Dosogne, Hoeben, Burvenich, and Lohuis () showed that cefapirin in therapeutic concentrations had no effect on phagocytic functions of cells isolated from bovine blood.…”
Section: Discussionmentioning
confidence: 99%
“…There are no literature data on the impact of antibiotics on the function of the immune system in the uterus. Most available published research shows the negative effects of many types of antibiotics on the phagocytic and killing activity of phagocytes, both in vitro and in vivo (Bode et al., ; Mor & Cohen, ; Pierce, Tarnow‐Mordi, & Cree, ). There are, however, publications that show the stimulating effects of certain antibiotics, e.g., cefaclor, on the phagocytic and bactericidal function of phagocytic cells (Dąbrowski & Stankiewicz, ).…”
Section: Discussionmentioning
confidence: 99%